Physical attributes of soil in different agricultural productions systems (Research, Society and Development, 2021)
In agricultural production systems, soil is the fundamental basis for acting as a physical and nutritious substrate for plants, guaranteeing the availability of water, air and other elements necessary for growth. Different production systems can subject the soil to a new state of equilibrium, affecting soil attributes, which can be favorable or unfavorable in its conservation. In this context, the study aimed to evaluate the effect of management on physical soil quality in different production systems. The research was carried out at the SAPÉ-AGRO farm in the municipality of Maracaju-MS, in soil classified as Red Latosol. The evaluated treatments were: sugarcane cultivation, pasture, corn cultivation under no-till system, oat cultivation under no-till system, crop-livestock integration and forest. The experimental design adopted was a completely randomized design. The physical quality data of the soil were subjected to analysis of variance, submitted to the Tukey test at 5% significance level. The physical attributes evaluated were soil density, macroporosity, microporosity, total porosity, geometric mean diameter and weighted mean diameter, at depths of 0-10 cm and 10-20 cm.